PENGUATAN GESER PADA KERETAKAN SENDI BETON BERTULANG DENGAN MENGGUNAKAN KOMPOSIT SERAT KARBON YANG DIPERKUAT PLASTIK (SKDP) - Eisenring, Maryo P (MEKTEK, 2012)
Carbon-fiber-reinforced plastic (CRFP), has over two decades become an increasingly notable material used in structural engineering application. CRFP could be used as prestressing materials due to their high strength. However research by improving the shear capacity of beam-column T-joints using CFRP composite materials is still in the early stages.The present paper describes some experimental results of unreal scale (one-third times the actual size) tests of concrete beam-column joints of several experiments by the Civil Construction Experts for 14 specimens. The variables considered were the composite system, the fiber orientation, and the surface preparation. The tests have demonstrated the viability of carbon FRP composites for their use in improving the shear capacity of the joints with inadequate confinement and their reinforcement analysis.